Working towards ethical management of genetic testing. - Parker, M; Lucassen, A (2002)
Developments in genetic testing and increased public awareness of inherited disease have led to increasing interest in and concern about the ethical issues raised by clinical genetics. We looked at methods for ethical management of genetic testing, and investigated the advantages and limitations of use of ethical guidelines in clinical genetics. We believe that a key element in successful management of genetic testing in addition to guidelines will be availability of ethics training and support for geneticists, nurses, and counsellors. Clinical ethics committees and clinical ethicists can act as a useful focus for such training and advice if their role is seen to be genuinely supportive by health professionals and patients. We also argue that increased public involvement at the national level in policy debate about control of genetic testing is needed.